Discrete Spawning Aggregations of the Loliginid Squid Doryteuthis gahi Reveal Life-History Interactions of a Dwarf Morphotype at the Center of Its Distribution Range - Carrasco, Sergio A.; Bravo, Macarena; Ibáñez, Christian M.; Zapata-Hernández, Germán (Frontiers in Marine Science, 2021)
Heterogeneous environmental conditions along the Humboldt Current System (HCS) influence the life-history strategy of a variety of species in different ways. There is limited information on latitudinal traits of coastal cephalopods as part of the interacting species in pelagic and benthic environments. The present study used the loliginid squid Doryteuthis gahi as a model organism to: (1) evaluate latitudinal traits on egg laying patterns, (2) characterize a particular spawning ground, (3) quantify the isotopic variation from different tissues, (4) evaluate potential trophic ontogenetic changes, (5) determinate trophic position, and (6) isotopically estimate the relative importance of putative preys in the squid’s assimilated diet. Results evidenced that egg-masses collected between 2014−2020 presented similar patterns along northern-central Chile (27–36°S), with females attaching small egg-capsules (10–50mm length) through the year and over a variety of anthropogenic and natural substrates. At a small scale (Coquimbo; 29°S), early life history traits showed distinct patterns depending on SST, with warmer collection periods (18°C) evidencing larger capsules and smaller embryos, although small paralarvae were obtained over the four-year sampling period. In this site, sampling of older ontogenetic stages supported the constant presence of small-sized squids (19–77mm ML). Males had larger mean sizes compared to females and undetermined specimens, with a high proportion of mature stages. Observations in captivity were extended for up to 110d, validating that small females (45–64mm ML) spawn the small egg-capsules typically observed in the field. Differences in stable isotope composition between beaks and soft tissues of adult squids were lower for δ13C values (1.1 vs 1.4‰, respectively) and higher for δ15N values (5.3 vs 4.7‰, respectively). Isotopic composition through ontogeny found similar δ13C and δ15N values, suggesting that carbon sources (pelagic origin) and trophic position did not change significantly, with copepods, euphausiids and nereid polychaetes being the most important preys. This study unveils the permanent occurrence of a small reproductive morphotype of D. gahi in shallow coastal habitats of northern-central Chile, providing the first insights for understanding the species’ potential adaptations to heterogeneous conditions in the HCS and the unexplored distribution gap between the two centers of abundance (Peru and the Falkland/Malvinas islands).